Cu,Zn Superoxide Dismutase Genes in Tribolium castaneum: Evolution, Molecular Characterisation, and Gene Expression during Immune Priming - Ferro, Kevin; Ferro, Diana; Corrà, Francesca; Bakiu, Rigers; Santovito, Gianfranco; Kurtz, Joachim (Frontiers in Immunology, 2017)
The production of Reactive Oxygen Species (ROS) is a normal consequence of the aerobic cell metabolism. Despite their high and potentially detrimental reactivity with various biomolecules, the endogenous production of ROS is a vital part of physiological, immunological and molecular processes that contribute to fitness. The role of ROS in host-parasite interactions is frequently defined by their contribution to innate immunity as effectors, promoting parasite death during infections. In vertebrates, ROS and antioxidant system enzymes, such as superoxide dismutase (SOD) are also involved in acquired immune memory, where they are responsible for T-cell signalling, activation, proliferation and viability. Based on recent findings, ROS are now also assumed to play a role in immune priming, i.e. a form of memory in invertebrates. In this study, the potential involvement of Cu,Zn SODs in immunity of the red flour beetle Tribolium castaneum is described for the first time, applying an approach that combines an in silico gene characterisation with an in vivo immune priming experiment using the Gram-positive entomopathogen Bacillus thuringiensis. We identified an unusually high number of three different transcripts for extracellular SOD and found that priming leads to a fine-tuned modulation of SOD expression, highlighting the potential of physiological co-adaptations for immune phenotypes.